ANALISIS PENGARUH EPS, EVA DAN CASH FLOW TERHADAP HARGA SAHAM PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI - Cristian Budi Santoso; Elma Muncar Aditya (Fakultas Ekonomi Universitas Pekalongan, 2015)
This research aimed to analyze the influence of Earning Per Share (EPS), Economic Value Added (EVA) and CashFlow to the stock price of food and beverage companies listed in Indonesian Stock Exchange in 2007-2010. Thepopulation in this research was 18 companies and the samples in this research were 16 food and beveragecompanies in Indonesia Stock Exchange in 2007-2010. The sampling technique used in this study was purposivesampling. While the analysis instrument in this research was the multiple linear regression. On the test coefficient of determination, the value of adjusted R square was 0.853, which meant theindependent variable EPS, EVA and Cash Flow could explain the variability of 85.3% of the dependent variablestock price. While the remaining 14.7% explained by other causes beyond the studied variables. Thesimultaneous regression testing (F-test) indicated that the variable EPS, EVA and Cash Flow had significantinfluence to the stock price. It could be proved from the F count (55.064) was bigger than F table (2.99). In thepartial regression testing (t-test), the variable earning per share (EPS) had siginificant influence to the stock pricewith t count (9.340) was bigger than t table (2.0595). Meanwhile, the economic value added (EVA) variable didnot influence the stock price with t count value (1.697) was smaller than t table value (2.0595) and the cash flowvariable also had no influence with the –t count (-0.726) was bigger than –t table (-2.0595). Keywords: Eearning Per Share (EPS), Economic Value Added (EVA),Cash Flow, Stock Price.